Sleep duration and perceptions of sleep quality in British Army recruits during basic training - an observational analysis - Rawcliffe, Alex J.; Tyson, Hayley; Hinde, Katrina; Jacka, Kimberley; Holland, Rachel; Chapman, Shaun; Roberts, Andrew J. (Frontiers in Neurology, 2024)
Sleep is critical to the health, wellbeing and performance of military personnel during basic training. This two-part study evaluated sleep-wake patterns and sleep disturbances in junior soldiers (JS) and infantry recruits in Autumn 2021 (study 1), and non-infantry recruits in spring 2022 (study 2). During studies 1 and 2, validated wearable technology combined with a sleep diary was used to quantify sleep-wake indices, sleep disturbances and perceptions of sleep quality. Sleep diary data was analysed descriptively. A series of repeated-measures ANOVAs examined differences in objective sleep-wake indices. Correlation analysis determined associations between time in bed (TIB) and total sleep time (TST). Significant (p<0.05) differences in most sleep-wake indices were observed between weeks of basic training for all cohorts. Strong positive correlations between TIB and TST were observed for each cohort across basic training (r = .681 -.970, p<0.001), with longer TST associated with greater TIB.